A quantitative study of hydration level of the skin surface and erythema on conventional and microclimate management capable mattresses and hospital beds. Issue 1 (February 2020) - Denzinger, Markus; Krauss, Sabrina; Held, Manuel; Joss, Leonard; Kolbenschlag, Jonas; Daigeler, Adrien; Rothenberger, Jens
Abstract: Background: In addition to pressure itself, microclimate factors are gaining more attention in the understanding of the development of pressure ulcers. While there are already various products to reduce pressure on sore-prone areas to prevent pressure ulcers, there are only a few mattresses/hospital beds that actively influence skin microclimate. In this study, we investigated if microclimate management capable mattresses/hospital beds can influence skin hydration and skin redness/erythema. Methods: We included 25 healthy subjects in our study. Measurements were made using Courage & Khazaka Multi Probe Adapter MPA with Corneometer CM825 and Mexameter MX18 to determine skin hydration of the stratum corneum and skin redness/erythema before and after the subjects were lying in conventional (Viskolastic® Plus, Wulff Med Tec GmbH, Fedderingen, Germany and Duo™ 2 mattress, Hill-Rom GmbH Essen, Germany) or microclimate management capable mattresses/hospital beds (ClinActiv + MCM™ and PEARLS AFT, Hill-Rom GmbH Essen, Germany). Results: While there was no difference in skin redness/erythema on the different mattresses/hospital beds, skin hydration of the stratum corneum decreased significantly in an air fluidized bed compared to baseline values and values measured on standard mattress/Viskolastic® Plus. Conclusion: Air-fluidized therapy reduces skin hydration and therefore could contribute to prevent moisture associated ulcers. Changes in skin hydration as one important factor of skin microclimate can be detected after a short time of incubation and even before an erythema appears.